A Study On Aircraft Air-Conditioning System Trainer Model AS-43 For Aeronautical Engineering Student Practice - Ezaiyuddin, Amirah Eitqan; Nor Salim, Nor Adrian (Progress in Aerospace and Aviation Technology, 2023)
Aircraft air conditioning systems are crucial for ensuring a comfortable and safe environment for occupants during flight. These systems regulate temperature, humidity, and air pressure within the cabin and are found in various aircraft types, including commercial airliners, business jets, military aircraft, and helicopters. The objectives of the research are to identify suitable standard operating procedures (SOPs) and safety protocols for the trainer system, and to determine temperature, relative humidity, pressure, and enthalpy changes within the AS-43 system. A varying parameter is temperatures, pressure, relative humidity and the enthalpy can be obtained. Manual Cool and Auto cool mode of the AS-43 trainer are evaluated. The experimental results show the Manual Cool and Auto Cool gives a slightly different enthalpy values and COP for the system. The enthalpy obtained from the Manual cool are between 240 kJ/kg to 450 kJ/kg while Auto Cool enthalpy is between 240 kJ/kg to 440 kJ/kg. The relative humidity of both modes is in average range suggested by ASHRAE. P-h diagram of both experiments can be obtained based on the data collected. Finally, the study focuses on the AS-43 Aircraft Air Conditioning System Trainer Model, which serves as a valuable educational tool for teaching students about aircraft air conditioning systems. Hence, a significant recommendation is suggested discussed at the end of the research.